1975
DOI: 10.1021/jo00892a009
|View full text |Cite
|
Sign up to set email alerts
|

Bromination and chlorination of 1,1,1-trifluoro-N-phenylmethanesulfonamides

Abstract: m/e 266 (M+), 338 (monosilylated product)4, 410 (disilylated product)4, 248 [monosilylated - (CHslgSiOH]4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Recently it was shown that a slight excess of fluorinated anhydride in the presence of excess of base was adequate for the formation of only mono-sulfonamides [16]. Trifluoromethanesulfonyl fluoride is known to give facile reactions with different amines yielding mono-sulfonamides [17]. In order to introduce the trifluoromethanesulfonyl moiety into Trifluoromethanesulfonamide-substituted azoles were synthesized by the reaction of 5-aminotetrazole, 3-amino-1,2,4-triazole and 3,5-diamine-1,2,4-triazole with trifluoromethanesulfonyl fluoride to prepare only monosubstituted compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was shown that a slight excess of fluorinated anhydride in the presence of excess of base was adequate for the formation of only mono-sulfonamides [16]. Trifluoromethanesulfonyl fluoride is known to give facile reactions with different amines yielding mono-sulfonamides [17]. In order to introduce the trifluoromethanesulfonyl moiety into Trifluoromethanesulfonamide-substituted azoles were synthesized by the reaction of 5-aminotetrazole, 3-amino-1,2,4-triazole and 3,5-diamine-1,2,4-triazole with trifluoromethanesulfonyl fluoride to prepare only monosubstituted compounds.…”
Section: Resultsmentioning
confidence: 99%
“…No N-halogenated products were obtained by chlorination or bromination of N -phenyltriflamide; instead, the halogenation occurred at the ortho and para positions of the aromatic ring. The reaction of N -phenyltriflamide with such electrophilic fluorinating reagents as fluoroxytrifluoromethane CF 3 OF and bis(fluoroxy)difluoromethane CF 2 (OF) 2 proceeds similarly .…”
Section: Trifluoromethanesulfonamides (Triflamides)mentioning
confidence: 97%